4CPS-162 Infliximab serum concentrations, antibody formation and clinical response in psoriatic patients. (2nd March 2018) - Colls, M; Padullés, N; Padullés, A; Notario, J; Bas, J; Fernández, C Mariño; Colom, H
Abstract : Background: A large variability in biopharmaceutical kinetics exists between patients and even within a patient over time. Also, adequate thorough concentrations are linked to response in psoriasis. Therapeutic drug monitoring of biopharmaceuticals (i.e. infliximab–IFX) together with clinical response allows targeted cost-effective dose-adjustments. Purpose: The aim of the present study was to evaluate the real-life association between IFX exposure and clinical outcomes in patients with psoriasis. Material and methods: Prospective study in psoriatic patients receiving IFX, between October 2013 and November 2016. We measured Cmin and antibodies towards IFX (ATI) using an enzyme-linked immunosorbent assay (ELISA) kit. Data on demographic, analytical and pharmacological variables and Psoriasis Area Severity Index (PASI) were recorded. Mixed models were estimated to evaluate association between IFX through concentrations (Cmin ) and clinical response. Statistical analysis was carried out using R. Results: We used a total of 155 Cmin values and ATI from 33 patients (33% females). Weight: 88.2 Kg (±23.5), BMI: 31 Kg/m 2 (±2.2), PASI at blood sampling: 2.2 (±3.2), PASI score reduction:% (±) (normal weight: 79% (±32.4), overweight: 78.2% (±35) and obese: 76.3% (±31)). Percentage of PASI 75, 90 and 100 response: 78.8%, 60.6% and 54.5%, respectively. The median Cmin was 2.4 mg/L (±2.2) (normal weight: 1.64 mg/L, overweight: 2.68 mg/L and obese: 2.68 mg/L). Six patients tested ATI positive and had undetectable Cmin . Patients achieving PASI 75 had a significantly higher Cmin than non-responders (2.86 vs 1.58 mg/L, p<0.001). Similar results were obtained for PASI 90 and 100 responses. PASI score was significantly influenced by Cmin (IRR: 0.79, 95% CI: 0.69 to 0.91). This remained significant when adjusting by sex, BMI, diagnose, baseline PASI, leukocyte count, ATI status and immunomodulator treatment (IRR: 0.80, 95% CI: 0.70 to 0.93). Same results were obtained for PASI 90 and 100 responses (OR: 1.79, 95% CI: 1.14 to 2.81; OR:.1.79, 95% CI: 1.18 to 2.71 respectively). Conclusion: PASI score and achievement of PASI 90 response or higher were significantly influenced by IFX Cmin . The percentage of patients achieving PASI 75 or higher decreased with BMI, while Cmin values increased. No conflict of interest